Decline in rate of death from ischaemic heart disease in the United Kingdom. Issue 6361 (22nd January 1983) - Heller, R F; Hayward, D; Hobbs, M S
Abstract : The rates of death from ischaemic heart disease in the United Kingdom in the years after 1968 were studied to establish whether any general trend had occurred. A decline in the rates began after 1973-4, was greatest in those aged 35-44 years, and occurred among both men and women and in each of the regions of England and in Wales and Scotland. Total dietary fat intake had started to fall about five years earlier, and this may provide part of the explanation. Changes in smoking habits also occurred but were more difficult to relate to the pattern of change in the death rates. If a general decline in ischaemic heart disease has begun in the United Kingdom a case may be made for close monitoring of changes in lifestyle and medical practice in different demographic groups to try to find the explanation.